Effect of Plant Growth Regulators on Yield and Quality in Gladiolus under Bay Island Conditions - V Baskaran; K Abirami; S Dam Roy (Journal of Horticultural Sciences, 2014)
Field experiments were conducted for two consecutive seasons during 2011-12 and 2012-13 to study the effect of plant growth regulators on gladiolus cv. Chandini. The results revealed that various growth, flowering and corm characters were significantly affected with the application of different growth regulators at different concentrations. Earliness in corm sprouting, spike emergence and maximum duration of spike was observed in GA3 500ppm. Maximum number of leaves per plant, plant height, maximum spike length, rachis length and number of florets per spike were observed in GA3 750ppm. More number of shoots per corm (3.3) was recorded by Benzyl Adenine (BA) at 75ppm. With respect to corm characters maximum number of corms and cormels per plant were observed in BA 100ppm. Maximum weight of single corm, weight of corms per plant, size of single corm and volume of single corm were recorded in GA3 500ppm. Maximum weight of cormels per plant was recorded in BA 100ppm. Maximum value of propagation coefficient was recorded in GA3 500ppm (318.3%).